High prevalence of Chlamydia trachomatis, Neisseria gonorrhoeae and particularly Trichomonas vaginalis diagnosed using US FDA‐approved Aptima molecular tests and evaluation of conventional routine diagnostic tests in Ternopil, Ukraine. Issue 9 (13th August 2019) - Boiko, Iryna; Golparian, Daniel; Krynytska, Inna; Unemo, Magnus
Abstract : Sexually transmitted infections (STIs) remain major public health problems globally. Appropriate laboratory diagnosis of STIs is rare in Ukraine. We investigated the prevalence of Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG) and Trichomonas vaginalis (TV) using the US FDA‐approved Aptima Combo 2 and Aptima TV assays and compared the results with the conventional routine diagnostic tests (CDTs) in Ukraine. Urogenital swabs from consecutive mostly symptomatic females (n = 296) and males (n = 159) were examined. The prevalences were as follows: 10% (n = 47) of TV, 5.3% (n = 24) of CT and 1.5% (n = 7) of NG. The specificity of some CDTs was high, for example, 100% for NG culture, TV IgG ELISA, CT IgM ELISA and CT microscopy, but lower for other CDTs, that is, from 44% to 99.8%. The sensitivity of all CDTs was suboptimal, that is, 71% (n = 5) for NG microscopy, 57% (n = 4) for NG culture, 53% (n = 8) for CT IgG ELISA, 33% (n = 1) for TV IgG ELISA, 28% (n = 13) for TV microscopy, 25% (n = 1) for CT IgA ELISA, 20% (n = 3) for CT IgM ELISA and 0% (n = 0) for CT microscopy. The prevalences of particularly TV and CT were high, but substantial also for NG, in Ternopil, Ukraine. The sensitivities of all CDTs were low, and widespread implementation of validated, quality‐assured and cost‐effective molecular diagnostic STI tests in Ukraine is imperative.